No one left behind : the Philippine financial inclusion journey - Banal-Formoso, Chelo; Bolido, Erlinda; Bangko Sentral ng Pilipinas (Malate, Manila, Philippines : Bangko Sentral ng Pilipinas, 2020)
This book gives an unprecedented look at the BSP's financial inclusion journey as told not only by us, but also by our advocates, champions, partners in industry and development, and, most important of all, the common men who give heart and meaning to our service. It features firsthand accounts and personal testimonies on financial inclusion's positive impact. It records how our initiatives were transformed from a seed of an idea scribbled on a whiteboard to bonafide institutional policies and action. Each chapter chronicles a step in our journey so far - the adoption of microfinance as an advocacy for poverty alleviation, the embrace of innovation for effective policy formulation and implementation, the ensuing impact of our initiatives, the eventual maturity into a thought leader, and, finally, what the future holds for the BSP and its financial inclusion work.
Includes bibliographical references (pages 188-191) and index.
In English.
Keywords: Bangko Sentral ng Pilipinas; Banks and banking, Central -- Philippines -- History